Age-Related Blood Pressure Sensitivity to Aldosterone in Blacks and Whites. Issue 1 (July 2018) - Tu, Wanzhu; Li, Ruohong; Bhalla, Vivek; Eckert, George J.; Pratt, J. Howard
Abstract : Aldosterone sensitivity, defined as the magnitude of the association of plasma aldosterone concentration with blood pressure (BP), seems to be a function of plasma volume. It increases as plasma renin activity decreases, and it is more significant in blacks but less so in whites. Age is a strong determinant of BP, and an increase in aldosterone sensitivity could contribute to the increase in BP. In the present study, we tested the hypothesis that aldosterone sensitivity increases with age. We used observational data collected from normotensive blacks and whites enrolled in a prospective cohort study. They were studied as children (248 blacks/357 whites) and again as young adults (74 blacks/125 whites) over an age range of 7 to 39 years. A varying-coefficient regression analysis was used to explore the influences of aldosterone on systolic BP. After controlling for body mass index, race, and sex, both plasma renin activity and plasma aldosterone concentration were lower in blacks, and their levels declined with age ( P <0.001). In blacks, plasma aldosterone concentration decreased 0.25 ng/dL per year; in whites, plasma aldosterone concentration decreased 0.18 per year. Aldosterone's effect on BP, characterized by a smooth function of age, intensified as age increased, especially in blacks ( P <0.01), suggesting an increased aldosterone sensitivity with age. In comparison to blacks, age-related changes in aldosterone sensitivity in whites were not statistically significant. These findings extend the rationale for targeting aldosterone in the treatment of hypertension, especially in blacks. Abstract : Supplemental Digital Content is available in the text.